LEGISLATIVE FORMATION OF THE BASES OF HARM INDEMNIFICATION IILEGALLY IMPOSED BY THE STATE DURING CRIMINAL PROSECUTION IN THE RUSSIAN EMPIRE PERIOD - B. A. Polyakov (Russian Journal of Economics and Law)
The article is devoted to the historical aspect of formation and development of the norms of harm indemnification imposed by unlawful criminal prosecution by the Russian law of 19th – beginning of 20th c.